The effects of nedocromil sodium on the response to grain dust in West Australian grain workers. Issue 10 (October 1990) - Blainey, A D; Musk, A W; Ryan, G; Phillips, M J; Buccilli, C; Troon, S; Kidd, G
Abstract : Seasonal grain workers in Western Australia who develop respiratory symptoms after exposure to grain dust develop concomitant changes in lung function and bronchial responsiveness to methacholine. The mechanisms underlying these changes are not known. A detailed study was undertaken of seasonal grain workers in Western Australia to evaluate the effect of nedocromil sodium (Fisons, United Kingdom) on these changes to see if they could be prevented by this drug. Forty seven subjects participated. Symptoms and forced expiratory volume in one second (FEV1) were recorded before the study and before, during, and after each working shift, and bronchial responsiveness to methacholine was measured at the beginning and end of the study. Twenty three subjects received nedocromil and 22 received a placebo in a double blind design; there was no difference in baseline characteristics between the two groups. At the end of the study, no differences were found between the nedocromil and placebo groups in the prevalence of symptoms or development of new symptoms during the study. The drug had no effect on changes in methacholine PD20 or FEV1. As in previous studies, new symptoms developing during the season were more common in atopic subjects and were associated with a fall in methacholine PD20. It is concluded that nedocromil has no effect on the development of new symptoms in grain workers. The mechanisms underlying these symptoms require further study.